Sleep quality and obesity in young subjects: a meta-analysis - Fatima, Y.; Doi, S. A. R.; Mamun, A. A. (Obesity reviews, 2016)
Summary Objectives To assess the effect of poor sleep quality on Overweight/Obesity (Ow/Ob) in young subjects, and explore if this association is independent of sleep duration. Methods Pubmed, EMBASE, and MEDLINE databases were searched for papers on sleep quality and overweight/obesity, focusing on children, adolescents, and young adults. Studies based on subjects with medical/psychological problems or published in languages other than English were excluded. Quality effects model was used to pool studies for meta‐analysis. Results Findings from the systematic review suggest a link between poor sleep quality and Ow/Ob in young subjects. Pooled estimate (from 26,553 subjects) suggest a role of inadequate sleep (including both short duration and poor quality) in Ow/Ob (OR: 1.27 95% CI: 1.05‐1.53). Sub‐group‐analyses suggest considerably higher odds of Ow/Ob (OR = 1.46, 95% CI: 1.24‐1.72) in young subjects with poor sleep quality (independent of duration). Conclusions Poor sleep quality seems to be associated with Ow/Ob, and some studies indicate this association to be independent of duration. Therefore, considering only sleep duration might not help in disentangling sleep‐obesity association. However, this review is mostly composed of cross‐sectional studies. Therefore, a causal link or the stability of the sleep quality and Ow/Ob association could not be established.